Total Mucosal Irradiation with Intensity-modulated Radiotherapy in Patients with Head and Neck Carcinoma of Unknown Primary: A Pooled Analysis of Two Prospective Studies. Issue 9 (September 2016) - Richards, T.M.; Bhide, S.A.; Miah, A.B.; Del Rosario, L.; Bodla, S.; Thway, K.; Gujral, D.M.; Rooney, K.P.; Schick, U.; McGovern, T.; Grove, L.; Newbold, K.L.; et al.
Abstract: Aims: To determine the clinical outcomes of an intensity-modulated radiotherapy technique for total mucosal irradiation (TM-IMRT) in patients with head and neck carcinoma of unknown primary (HNCUP). Materials and methods: A single-centre prospective phase II trial design was used in two sequential studies to evaluate TM-IMRT for HNCUP. Patients were investigated for primary tumour site using examination under anaesthetic and biopsies, computed tomography ± magnetic resonance imaging (MRI) or 18-fluorodeoxyglucose positron emission tomography-computed tomography (PET-CT). Patients received IMRT to the potential primary tumour sites and elective cervical nodes. Concomitant chemotherapy was used in patients who received primary radiotherapy or those with nodal extracapsular extension. Results: Thirty-six patients with HNCUP were recruited; 72% male. Twenty-five patients (69.4%) had p16-positive disease. Two year mucosal and local nodal control rates were 97.1% (95% confidence interval 91.4–100) and 89.8% (78.4–100), respectively. One mucosal primary was detected 7.3 months after TM-IMRT and three patients died from recurrent/metastatic squamous cell carcinoma of the head and neck. Twelve patients (33%) developed grade 3 (Late Effects in Normal Tissue-Subjective, Objective, Management and Analytical; LENT-SOMA) dysphagia with a 1 year enteric tube feeding rate of 2.7%. The high-grade subjective xerostomia rate (LENT-SOMA) at 24 months after IMRT was 15%. Conclusions: At a median follow-up of 36.1 months, the use of TM-IMRT was associated with good local control. Toxicity was comparable with previously reported TM-IMRT regimens encompassing similar mucosal volumes. Highlights: We assessed outcomes of total mucosal irradiation in patients with head and neck carcinoma of unknown primary. A single-centre phase II trial design in two sequential studies evaluated one intensity-modulated radiotherapy technique. Good local control and survival rates were seen. Toxicity was improved compared with similar TM-IMRT regimens encompassing similar mucosal volumes.